Dyslipidemia and aortic valve disease. Issue 6 (8th December 2021) - Mata, Pedro; Alonso, Rodrigo; Pérez de Isla, Leopoldo; Badimón, Lina
Abstract : Purpose of review: Degenerative aortic stenosis (AS) is one of the most prevalent heart valve diseases in the adult population. The understanding of AS pathophysiology and involved risk factors have recently undergone a great advance, with low-density lipoprotein cholesterol (LDL-C), lipoprotein (a) [Lp(a)] and other clinical conditions taking on a relevant role. Although little is known about the prevention of AS, we can progressively find more evidence of the possible use of drugs to control risk factors as tools that may delay the progression to severe AS and aortic valve replacement. Recent findings: Several factors have shown to be solid predictors of the development of AS. Mendelian randomization and observational studies on risk factors specifically lipid factors, such as hypercholesterolemia, Lp(a), proprotein convertase subtilisin/kexin type 9 and hypertension have provided meaningful new information. The SAFEHEART study has significantly contributed to define the role of LDL-C and Lp(a) in AS. Summary: In this review we discuss the interrelationship of dyslipidemia, especially hypercholesterolemia and Lp(a) in the development and prognosis of valvular AS. New imaging tools may contribute to its early detection. Future studies with proprotein convertase subtilisin/kexin type 9 inhibitors and specific therapies to lower Lp(a) might contribute to delay AS development.